2019
DOI: 10.1177/0046958019842000
|View full text |Cite
|
Sign up to set email alerts
|

Does Public Health Insurance Coverage Lead to Better Health Outcomes? Evidence From Chinese Adults

Abstract: This article examines the impacts of public health insurance on the health of adults through use of data from the China Health and Nutrition Survey. We use the endogenous treatment effects model to infer the causal effects of public health insurance on health. We find that public health insurance significantly improves the physical and mental health status of health insurance beneficiaries after controlling for other covariates. Among the 2 types of voluntary public health insurance, the Urban Resident Basic M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 33 publications
(37 reference statements)
3
19
0
Order By: Relevance
“…Due to the differences in social-economic status, differences will also exist in the level of understanding of TB. A study conducted among Chinese adults suggested that medical insurance for urban workers had the greater impact on improving health-related behaviors than the NCMS [37]. This may be the reason why people who were insured under the medical insurance for urban workers scheme had a higher rate of awareness of TB.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the differences in social-economic status, differences will also exist in the level of understanding of TB. A study conducted among Chinese adults suggested that medical insurance for urban workers had the greater impact on improving health-related behaviors than the NCMS [37]. This may be the reason why people who were insured under the medical insurance for urban workers scheme had a higher rate of awareness of TB.…”
Section: Discussionmentioning
confidence: 99%
“…24 Fan et al discovered that public health insurance significantly improves the physical and mental health of health insurance beneficiaries after controlling for other covariates. 25 Pan et al concluded that Urban Resident Basic Medical Insurance (URBMI) beneficiaries experience statistically better health than the uninsured. 26 Finkelstein et al, using a randomized controlled design, found that health insurance in Oregon significantly improved the self-reported physical and mental health of the insured.…”
Section: Introductionmentioning
confidence: 99%
“…25 Fan H (2019) compared the healthcare utilization of the insured between the BMISUR and NRCMS, and showed that healthcare utilization was higher among BMISUR participants than among NRCMS participants, with the BMISUR improving health to a greater extent than the NRCMS. 26 Gong X (2019) studied the effects of social medical insurance (BMISUE and BMISUR) on the utilization of hospice medical services of elder adults. found that under the same conditions, either BMISUE or BMISUR can significantly improve the utilization level of hospice medical services for the elderly, but the total hospice expenditure of the elderly covered by BMISUE is 33.11% higher than that of BMISUR.…”
Section: Introductionmentioning
confidence: 99%